Intersection Points of Hurufism And Alevi-Bektashi Belief System Within The Framework of God-Universe-Human Conception (Journal of Alevism-Bektashism Studies, 2024)
From ancient times to the present, humanity has pondered the nature of God and the human position in the universe and in relation to God. This issue has constituted one of the main subjects of both philosophy and religions.This issue has been a fundamental problematic in Turkish and Islamic thought traditions. The Hurufi and Alevi-Bektashi belief systems have interacted within a religious, historical, and political framework, and as a result, both belief systems have emerged as two aspects of the same world of thought and belief. The common world of belief in both systems has primarily manifested itself in the conception of God-universe-human. The fundamental proposition of the conception of God-universe-human in both belief systems is that existence emanates from the “one” and especially that the human is the manifestation of the divine. The thought known as vahdet-i vücûd (unity of existence), which proclaims the unity of beings, has influenced the views of every sect and school of thought in Islamic tradition, yet in the Hurufism and Alevi-Bektashi belief system, this view has been uniquely interpreted. At the core of this unique thought lies a shared understanding of the human. In this study, the intersections of the Hurufism and Alevi-Bektashi belief system are examined, thereby arguing that, despite developing different methods and original ideas, the conception of God-universe-human in the two belief systems is built upon the same conceptual foundation. İn order to explain this approach, in this study examples were given and evaluated from literature and works that reflect the belief world of both Hurufism and the Alevi Bektashi belief system. As a result, the emphasis on common tradition in the context of both beliefs bas been tried to be concretely proven.